ANALISIS PROBLEMATIKA GURU SD NEGERI 01 PULAU BERINGIN DALAM PENERAPAN KURIKULUM MERDEKA - Inda Widiana Inda; Murjainah; Aswadi Jaya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to describe the problems faced by teachers in the implementation of the Merdeka Curriculum. The research method used is a descriptive qualitative approach with data collection techniques through interviews, questionnaires, and documentation. The research results show that in the independent curriculum planning process, what teachers do is to prepare learning such as teaching modules and learning media related to the material to be taught and the principal also conducts training in schools to provide insight into the implementation of the independent curriculum. In its implementation, elementary school 01 Pulau Beringin teachers apply learning by using various methods such as using video-based learning media, photos displayed with infocus in implementing an independent curriculum. However, some teachers have difficulty understanding the concepts and techniques of implementing independent curricula, especially for senior teachers who experience limitations in compiling learning plans such as ATP and teaching modules, there are obstacles in carrying out project-based learning, low skills of senior teachers in using technology, and difficulties for teachers to change learning methods. The evaluation stage of the method used by the teacher is to use an assessment to see the student's learning achievements, both daily repetitions, mid-semester tests, and end-of-semester assessments. In overcoming the problems that occur, every homeroom teacher has a companion teacher who can help implement an independent curriculum to help the homeroom teacher in learning in the classroom.